Dynamics of evidence-informed health policy making in Pakistan. Issue 10 (17th October 2017) - Haq, Zaeem; Hafeez, Assad; Zafar, Shamsa; Ghaffar, Abdul
Abstract: Incorporating evidence is fundamental to maintaining the general acceptance and efficiency in public policies. In Pakistan, different actors—local and global—strive to facilitate the development of evidence-informed health policies. Effective involvement however, requires knowledge of the country-context, i.e. knowing the intricacies of how policies are formulated in Pakistan. Obtaining this knowledge is one of the key steps to making interventions impactful.  We carried out a qualitative study to explore the environment of evidence-informed health policy in Pakistan. The study involved 89 participants and comprised three phases including: (1) literature review followed by a consultative meeting with key informants to explore the broad contours of policy formulation, (2) in-depth interviews with participants belonging to various levels of health system to discuss these contours and (3) a roundtable with experts to share and solidify the findings.  Policy development is a slow, non-linear process with variable room for incorporation of evidence. Political actors dominate decisions that impact all aspects of policy, i.e. context, process and content. Research contributions are mostly influenced by the priorities of donor agencies—the usual proponents and sponsors of the generation of evidence. Since the devolution of health system in 2012, Pakistan's provinces continue to follow the same processes as before 2012, with little capacity to generate evidence and incorporate it into health policy.  This study highlights the non-systematic, nearly ad hoc way of developing health policy in the country, overly dominated by political actors. Health advocates need to understand the policy process and the actors involved if they are to identify points of impact where their interaction with policy brings the maximum leverage. Moreover, an environment is needed where generation of data gains the importance it deserves and where capacities are enhanced for communicating and understanding evidence, as well as its incorporation into policy.